Protein coevolution and isoexpression in yeast macromolecular complexes - Ettwiller, Laurence; Veitia, Reiner A. (International journal of genomics, 2006)
Previous studies in the yeast Saccharomyces cerevisiae have shown that genes encoding subunits of macromolecular complexes have similar evolutionary rates (K) and expression levels (E). Besides, it is known that the expression of a gene is a strong predictor of its rate of evolution (i.e., E and K are correlated). Here we show that intracomplex variation of subunit expression correlates with intracomplex variation of their evolutionary rates (using two different measures of dispersion). However, a similar trend was observed for randomized complexes. Therefore, using a mathematical transformation, we created new variables capturing intracomplex variation of both E and K. The values of these new compound variables were smaller for real complexes than for randomized ones. This shows that proteins in complexes tend to have closer expressivities (E) and K's simultaneously than in the randomly grouped genes. We speculate about the possible implications of this finding.